(3Yjhf GdJhGQjNs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , J (B764 (3g` s; (3KGHJ Hf CHj KGHJ SYjO Gdchaj , CHh eMeO,J (B250 (3g` s
(3ChdgG (B:s
(3ef SfI (B645 s
(3BNQgG (B:s
(3Edi SfI (B670 s
(3fSNI YdjgG NWhW cKjQ ef eTGgjQ GdYdeGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B97 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B100 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B248s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B189 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs